Influence of electron-phonon interaction on the properties of transport through double quantum dot with ferromagnetic leads - 罗侃 王发强 梁瑞生 任珍珍 (Chinese physics B, 2014)
Electronic transport through a vibrating double quantum dot （DQD） in contact with noncollinear ferromagnetic （FM） leads is investigated. The state transition between the two dots of the DQD is excited by an AC microwave driving field. The corresponding currents and differential conductance are calculated in the Coulomb blockade regime by means of the Born-Markov master equation. It is shown that the interplay between electrons and phonons gives rise to phonon-assisted tunneling resonances and Franck-Condon blockade under certain conditions. In noncollinear magnetic configurations, spin-blockade effects are also observed, and the angle of polarization has some influence on the transport characteristics.